Method for electrochemical synthesis of hexamethylenediamine from acrylonitrile

By performing two stages of electrolytic reactions in two diaphragmless electrolytic cells A and B, the acrylonitrile reaction is converted into hexanediamine in one step, which solves the problems of high toxicity and complicated steps in the existing hexanediamine production process, and realizes an efficient and environmentally friendly hexanediamine synthesis process.

CN120041847AActive Publication Date: 2025-05-27WANHUA CHEM GRP CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311588822.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-05-27
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

In the existing hexadiene production process, the raw material adiponitrile is highly toxic, the steps are complicated, and the cost is high, making it difficult to meet the needs of future competition.

Method used

Acrylonitrile is used as raw material and is carried out in two electrolytic cells A and B through two stages of membrane-free electrolytic reactions. Quaternary ammonium base and phosphate are used as electrolyte components to control the electrolytic conditions to achieve efficient synthesis of hexanediamine.

Benefits of technology

The process of directly synthesizing hexanediamine in one-step reaction of acrylonitrile is realized, the process is simplified, the wastewater discharge is reduced, the molecular utilization rate is improved, and it has high practical value and environmental protection performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the method, electrolysis is divided into two sections, a lead electrode is used as a cathode in the first section of electrolysis, a nanometer titanium dioxide array tube electrode is used as the cathode in the second section of electrolysis, anodes used in the two sections of electrolysis are DSA anodes with iridium tantalum coatings, and electrolyte comprises acrylonitrile, phosphate and quaternary ammonium base. And injecting the electrolyte into an electrolytic cell for two-stage electrolytic reaction to obtain hexamethylenediamine, a small amount of propylamine and a small amount of 1, 3, 6-hexanetriamine. According to the process, hexamethylenediamine is directly synthesized from acrylonitrile by using an electrochemical method, so that the process is simple, few three wastes are generated, and the practical value is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical synthesis, and specifically relates to a method for electrochemically synthesizing hexamethylenediamine from acrylonitrile. Background Art

[0002] The production methods of hexamethylenediamine have always been only adiponitrile method, hexanediol method and caprolactam method. Among them, the preparation of hexamethylenediamine by hydrogenation of adiponitrile is almost the consensus of the global industrial community, and the production methods of adiponitrile are mainly butadiene method, acrylonitrile electrolytic dimerization method and adipic acid catalytic ammoniation method.

[0003] For a long time, adiponitrile in China has completely relied on imports, and its price has always been high, seriously affecting the economic benefits and international market competitiveness of China's nylon industry, and restricting the development of China's nylon 66 and related industries. However, since 2022, China has overcome the preparation method of adiponitrile, and for a while, China's adiponitrile production capacity and planned production capacity have shown an explosive state. It can be foreseen that the hexamethylenediamine industry will also enter a full competition stage of competing on cost and technology in the near future. In order to cope with the upcoming red ocean competition, we need to find a new, lower-cost and shorter-process synthetic route for hexamethylenediamine.

[0004] CN109647419A discloses a method for catalytic hydrogenation of adiponitrile to hexamethylenediamine with an alumina-supported nickel-based catalyst as the active component in a kettle reactor. From the existing literature and technologies, the raw material adiponitrile in the industrialized route of hydrogenation of adiponitrile to hexamethylenediamine is highly toxic and the steps are relatively cumbersome. Therefore, finding a method for directly synthesizing hexamethylenediamine from low-cost raw materials in one-step reaction is a very valuable research direction.

[0005] US5266731A discloses a method for electrochemically reducing nitriles to amines, but it faces problems such as the need for a diaphragm in electrolysis, cumbersome process, and difficult electrode preparation. We urgently need to find a simple series connection method, that is: without changing the electrolyte, using a diaphragm-free electrolysis method to reduce acrylonitrile in two steps to obtain hexamethylenediamine. Summary of the Invention

[0006] The present invention provides an electrochemical synthesis method for preparing hexamethylenediamine. Using this method to prepare hexamethylenediamine has a simple process and extremely little three wastes, and has high practical value.

[0007] To achieve the above invention purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for electrochemically synthesizing hexamethylenediamine from acrylonitrile, the method comprising the following steps:

[0009] (1) Mix acrylonitrile, quaternary ammonium base, phosphate, and water to prepare an electrolyte;

[0010] (2) The electrolyte is introduced into two diaphragmless electrolytic cells A and B for two-stage electrolytic reaction to produce hexamethylenediamine.

[0011] In the present invention, the quaternary ammonium hydroxide described in step (1) is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltriethylammonium hydroxide, and adamantylammonium hydroxide.

[0012] In the present invention, the content of the quaternary ammonium hydroxide in the electrolyte prepared in step (1) is 0.01 wt% - 5 wt%.

[0013] In the present invention, the phosphate described in step (1) is one or more of dipotassium hydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, and sodium dihydrogen phosphate;

[0014] In the present invention, the content of the phosphate in the electrolyte prepared in step (1) is 5 wt% - 12 wt%.

[0015] In the present invention, in the electrolyte described in step (1), the acrylonitrile content is 1 wt% - 20 wt%, and preferably, the acrylonitrile content in the electrolyte is 5 wt% - 15 wt%;

[0016] Both electrolytic cells A and B used in the present invention are single-chamber diaphragmless electrolytic cells. A DC power supply is used, and the constant current method is adopted to electrolyze the electrolyte, and the voltage is strictly controlled below 10 V to prevent the side reaction of hydrogen evolution from electrolyzed water from intensifying.

[0017] In the present invention, in step (2), when the reactant conversion rate in electrolytic cell A reaches 60 - 100%, it is switched to electrolytic cell B, and when the reactant conversion rate in electrolytic cell B is 60 - 100%, the electrolysis is stopped; preferably, when the reactant conversion rate in electrolytic cell A is 70 - 90%, it is switched to electrolytic cell B, and when the reactant conversion rate in electrolytic cell B is 70 - 90%, the electrolysis is stopped.

[0018] In the present invention, in step (2), the electrolytic reaction temperature in electrolytic cells A and B is 20 - 50 °C.

[0019] In the present invention, in step (2), the current density in electrolytic cell A is 500 A / m 2 - 3000 A / m 2 , and the current density in electrolytic cell B is 1500 A / m 2 - 3000 A / m 2 ; The electrodes in electrolytic cell A are a lead cathode and a DSA anode coated with iridium tantalum.

[0020] In the present invention, in step (2), the electrolytic anode in the B electrode tank is a DSA electrode with an iridium tantalum coating, and the electrolytic cathode is a nano-titanium dioxide array tube electrode, preferably a metal-doped modified titanium-based titanium dioxide array tube electrode. The doped metal is one or more of In, Ir, Zn, Sn, Pb, Ce, Zr, Fe, and Cu, and the doping amount is 1-50 mg / cm 2 ;

[0021] The preparation method thereof is: anodize a titanium sheet to obtain a nano-titanium dioxide array tube electrode, and then use the impregnation method to load other metals to obtain a metal-doped modified titanium-based titanium dioxide array tube electrode;

[0022] In a specific embodiment, the preparation method of the metal-doped modified titanium-based titanium dioxide array tube electrode includes:

[0023] a) Using a pure titanium plate as the substrate and a hydrofluoric acid solution as the anodizing solution, anodize it to obtain a nano-titanium dioxide array tube electrode;

[0024] Preferably, the concentration of the hydrofluoric acid solution is 0.01 wt%-10 wt%, the anodizing voltage is 5-50 V, and the time is 0.5-2 h.

[0025] b) Immerse the nano-titanium dioxide array tube electrode in a metal salt solution and calcine it to obtain a metal-doped modified titanium-based titanium dioxide array tube electrode;

[0026] The metal salt is a nitrate of one or more of In, Ir, Zn, Sn, Pb, Ce, Zr, Fe, and Cu;

[0027] Preferably, the total mass fraction of the metal salt in the immersion solution is 2-15 wt%, the immersion time is 1-4 h; the calcination temperature is 400-600 °C, and the calcination time is 1-3 h.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention adopts two-stage electrolysis to synthesize hexamethylenediamine from acrylonitrile in one step. The synthesis route is short, the process is simplified, and almost no wastewater is generated. The molecular utilization rate is high, and it is green and environmentally friendly. Specific Embodiments

[0030] The following specifically and detailedly describes the embodiments of the present invention. The embodiments are implemented on the premise of the technical solution of the present invention. Although it is impossible to list them all, representative detailed implementation manners and specific operation processes are given according to the experimental results. The protection scope of the present invention is not limited to the following embodiments.

[0031] DSA electrode with an iridium tantalum coating: the iridium tantalum DSA electrode of Suzhou Fenggang Titanium Materials;

[0032] All other raw materials mentioned in this article are conventional commercially available raw materials.

[0033] The analysis method uses gas chromatography to analyze the product. Conditions: Agilent gas chromatography, HP-5 chromatographic column for on-line determination, two-stage programmed temperature rise, initial temperature 20 °C, hold for 1 minute and then rise to 50 °C at a rate of 5 °C / min; then rise to 280 °C at a rate of 10 °C / min. Carrier gas high-purity N 2 , split ratio 100:1. Injection temperature 180 °C, detector is FID, detector temperature 280 °C.

[0034] Example 1

[0035] Electrode preparation:

[0036] The pure titanium substrate is polished with 600, 1500, and 5000-mesh sandpapers, ultrasonically cleaned in absolute ethanol for 10 min, and then placed in an oven to dry for later use.

[0037] Prepare 100 g of an aqueous solution containing 0.05 wt% hydrofluoric acid. Use the treated pure titanium substrate as the anode and a graphite electrode as the cathode, and oxidize for 1 h at a voltage of 5 V to obtain a nano-titanium dioxide array tube electrode. Take it out and immerse it in deionized water for 5 min, then place it in an oven and bake for 20 min until completely dry, and then weigh it.

[0038] Weigh 2 g of indium nitrate and 1 g of zirconium nitrate, add them to deionized water to prepare 100 g of an impregnation solution. Immerse the dried nano-titanium dioxide array tube electrode in the impregnation solution for 4 h, take it out, place it in deionized water and wash it for 30 s, then put it into a muffle furnace and calcine it at 400 °C for 2 h, and cool it with the furnace. The metal doping amount is obtained by the differential weight method as 11 mg / cm 2 of the modified titanium-based titanium dioxide array tube electrode.

[0039] Electrolysis reaction:

[0040] Weigh 2 g of acrylonitrile, 20 g of dipotassium hydrogen phosphate, and 1 g of tetraethylammonium hydroxide, add them to deionized water to prepare 200 g of an electrolyte solution, and pour it into a single-chamber electrolytic cell (Cell A) with a 4 cm 2 lead electrode as the cathode and a 4 cm 2 DSA electrode with an iridium-tantalum coating as the anode. The electrolytic cell is equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Start electrolysis when the temperature of the electrolyte solution reaches 30 °C. During the reaction, control the current density to be 500 A / m 2 , the temperature of the condenser is 15 °C, and constant current electrolysis is carried out, controlling the maximum voltage not to exceed 10 V. Calculate the theoretical reaction time required for complete reaction to be 5.05 h, and cut off the power supply after reacting for 4 h.

[0041] Pour the reaction solution in tank A into tank B, where tank B is a single-chamber electrolytic cell composed of a metal-doped modified titanium-based titanium dioxide array tube electrode as the cathode and a DSA electrode with an iridium-tantalum coating as the anode, both with a length of 4 cm. Tank B is also equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Electrolysis starts when the electrolyte temperature reaches 40 °C. Control the current density at 1500 A / m 2 and the temperature of the condenser at 15 °C, and control the maximum voltage not to exceed 10 V for constant-current electrolysis. Calculate that the theoretical reaction time required for complete reaction is 6.73 h, and cut off the power supply after reacting for 6 h. 2 Take samples for analysis, and obtain a conversion rate of raw material acrylonitrile of 80%, a selectivity of product hexamethylenediamine of 83%, a selectivity of main by-product adiponitrile of 5%, a selectivity of propylamine of 8%, and a selectivity of hexamethylenetriamine of 2%. 2 Example 2

[0042] Electrode preparation:

[0043] After polishing the pure titanium substrate with 600, 1500, and 5000-mesh sandpapers, ultrasonically clean it in absolute ethanol for 10 min, and then put it in an oven to dry for later use.

[0044] Prepare 100 g of an aqueous solution containing 1 wt% hydrofluoric acid. Use the treated pure titanium substrate as the anode and a graphite electrode as the cathode, and oxidize it at a voltage of 25 V for 0.5 h to obtain a nano-titanium dioxide array tube electrode. Take it out, immerse it in deionized water for 5 min, and then put it in an oven to bake for 20 min until completely dry, and then weigh it.

[0045] Weigh 10 g of zirconium nitrate, 0.5 g of iridium nitrate, and 1 g of lead nitrate, add them to deionized water to make 100 g of an impregnation solution. Immerse the dried nano-titanium dioxide array tube electrode in the impregnation solution for 4 h. Take it out, immerse it in deionized water for 30 s, and then put it in a muffle furnace and calcine it at 450 °C for 3 h, and cool it with the furnace. The metal doping amount of the modified titanium-based titanium dioxide array tube electrode is obtained as 35 mg / cm

[0046] Electrolysis reaction:

[0047] Weigh 10 g of acrylonitrile, 24 g of dipotassium hydrogen phosphate, 0.5 g of tetrabutylammonium hydroxide, and 0.4 g of adamantylammonium hydroxide, add them to deionized water to make 200 g of an electrolyte solution, and pour it into a tank with a 2 lead electrode as the cathode and a 4-cm-long

[0048] DSA electrode with an iridium-tantalum coating as the anode.

[0049] ... (The text seems to be incomplete here. It should continue with the description of the electrolysis process similar to Example 1.) 2 lead electrode as the cathode and a 4-cm-long 2In a single-chamber electrolytic cell (Cell A) with an iridium-tantalum-coated DSA electrode as the anode, the electrolytic cell is equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Electrolysis starts when the electrolyte temperature reaches 40 °C. During the reaction, the current density is controlled at 1500 A / m 2 , the temperature of the condenser is 15 °C, and electrolysis is carried out at a constant current, controlling the maximum voltage not to exceed 10 V. The theoretically required reaction time for complete reaction is calculated to be 8.62 h, and the power supply is cut off after 6.90 h of reaction time.

[0050] Pour the reaction solution in Cell A into Cell B, where Cell B is a single-chamber electrolytic cell composed of a metal-doped modified titanium-based titanium dioxide array tube electrode as the cathode and an iridium-tantalum-coated DSA electrode as the anode with dimensions of 4 cm 2 × 4 cm. 2 Cell B is also equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Electrolysis starts when the electrolyte temperature reaches 30 °C. Control the current density at 2500 A / m 2 , the temperature of the condenser is 15 °C, and electrolysis is carried out at a constant current, controlling the maximum voltage not to exceed 10 V. The theoretically required reaction time for complete reaction is calculated to be 20.10 h, and the power supply is cut off after 18 h of reaction time.

[0051] Sampling and analysis shows that the conversion rate of raw material acrylonitrile is 90%, the selectivity of the product hexamethylenediamine is 88%, the selectivity of the main by-product adiponitrile is 3%, the selectivity of propylamine is 4%, and the selectivity of hexamethylenetriamine is 4%.

[0052] Example 3

[0053] Electrode preparation:

[0054] After polishing the pure titanium substrate with 600, 1500, and 5000-mesh sandpapers, ultrasonically clean it in absolute ethanol for 10 min, and then place it in an oven to dry for later use.

[0055] Prepare 100 g of an aqueous solution containing 8 wt% hydrofluoric acid. Use the treated pure titanium substrate as the anode and a graphite electrode as the cathode, and oxidize it at a voltage of 50 V for 1.5 h to obtain a nano-titanium dioxide array tube electrode. Take it out, soak it in deionized water for 5 min, and then place it in an oven to dry for 20 min until completely dry and weigh it.

[0056] Weigh 2 g of zirconium nitrate, 5 g of cerium nitrate, 1 g of tin nitrate, and 1 g of iron nitrate and add them to deionized water to prepare 100 g of an impregnation solution. Immerse the dried nano-titanium dioxide array tube electrode in the impregnation solution for 4 h. Take it out, soak it in deionized water for 30 s, and then place it in a muffle furnace to calcine at 500 °C for 2 h, and cool it with the furnace. The metal doping amount is obtained by the differential weight method to be 29 mg / cm 2 of the modified titanium-based titanium dioxide array tube electrode.

[0057] Electrolysis reaction:

[0058] Weigh 20 g of acrylonitrile, 15 g of dipotassium hydrogen phosphate, 2 g of tetrabutylammonium hydroxide, 0.5 g of benzyltriethylammonium hydroxide, and 0.5 g of tetrapropylammonium hydroxide, add them to deionized water, prepare an electrolyte solution of 200 g, and pour it into a single-chamber electrolytic cell (Cell A) with a 4-cm 2 lead electrode as the cathode and a 4-cm 2 DSA electrode with an iridium-tantalum coating as the anode. The electrolytic cell is equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Start electrolysis when the temperature of the electrolyte solution reaches 25 °C. During the reaction, control the current density at 3000 A / m 2 , the temperature of the condenser is 15 °C, perform constant-current electrolysis, and control the maximum voltage not to exceed 10 V. Calculate the theoretical reaction time required for complete reaction to be 8.62 h, and cut off the power supply after reacting for 6.90 h.

[0059] Pour the reaction solution in Cell A into Cell B, where Cell B has a 4-cm 2 metal-doped and modified titanium-based titanium dioxide array tube electrode as the cathode and a 4-cm 2 DSA electrode with an iridium-tantalum coating as the anode to form a single-chamber electrolytic cell. Cell B is also equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Start electrolysis when the temperature of the electrolyte solution reaches 40 °C. Control the current at 3000 A / m 2 , the temperature of the condenser is 15 °C, perform constant-current electrolysis, and control the maximum voltage not to exceed 10 V. Calculate the theoretical reaction time required for complete reaction to be 33.50 h, and cut off the power supply after reacting for 30.02 h.

[0060] Sampling and analysis show that the conversion rate of the raw material acrylonitrile is 85%, the selectivity of the product hexamethylenediamine is 85%, the selectivity of the main by-product adiponitrile is 4%, the selectivity of propylamine is 0.8%, and the selectivity of hexamethylenetriamine is 9%.

[0061] Example 4

[0062] Electrode preparation:

[0063] After polishing the pure titanium substrate with sandpapers of 600, 1500, and 5000 meshes, ultrasonically clean it in absolute ethanol for 10 min, and then put it in an oven to dry for later use.

[0064] Prepare 100 g of an aqueous hydrofluoric acid solution containing 1 wt%, use the treated pure titanium substrate as the anode and a graphite electrode as the cathode, oxidize it at a voltage of 25 V for 0.5 h to obtain a nano-titanium dioxide array tube electrode. Take it out, soak it in deionized water for 5 min, and then put it in an oven to bake for 20 min until it is completely dry.

[0065] Put it in a muffle furnace and calcine it at 450 °C for 2 h, and cool it with the furnace to obtain an ordinary titanium dioxide array tube electrode without metal doping and modification.

[0066] Electrolytic reaction:

[0067] Weigh 10 g of acrylonitrile, 15 g of dipotassium hydrogen phosphate, 5 g of tetrabutylammonium hydroxide, and 0.4 g of adamantylammonium hydroxide, add them to deionized water, prepare an electrolyte solution of 200 g, and pour it into a single-chamber electrolytic cell (Cell A) with a 4-cm 2 lead electrode as the cathode and a 4-cm 2 DSA electrode with an iridium-tantalum coating as the anode. The electrolytic cell is equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Start electrolysis when the temperature of the electrolyte solution reaches 40 °C. During the reaction, control the current density to be 1500 A / m 2 , the temperature of the condenser is 15 °C, and perform constant-current electrolysis, controlling the maximum voltage not to exceed 10 V. Calculate that the theoretical reaction time required for complete reaction is 8.62 h, and cut off the power supply after reacting for 6.90 h.

[0068] Pour the reaction solution in Cell A into Cell B, where Cell B has a 4-cm 2 ordinary titanium dioxide array tube electrode as the cathode and a 4-cm 2 DSA electrode with an iridium-tantalum coating as the anode to form a single-chamber electrolytic cell. Cell B is also equipped with a serpentine condenser, and an oil bath is used to control the temperature of the electrolytic cell. Start electrolysis when the temperature of the electrolyte solution reaches 30 °C. Control the current density to be 2500 A / m 2 , the temperature of the condenser is 15 °C, and perform constant-current electrolysis, controlling the maximum voltage not to exceed 10 V. Calculate that the theoretical reaction time required for complete reaction is 20.10 h, and cut off the power supply after reacting for 18 h.

[0069] Take samples for analysis, and obtain that the conversion rate of the raw material acrylonitrile is 77%, the selectivity of the product hexamethylenediamine is 35%, the selectivity of the main by-product adiponitrile is 45%, the selectivity of propylamine is 10%, and the selectivity of hexamethylenetriamine is 4%.

[0070] Comparative Example 1

[0071] Compared with Example 2, two-stage electrolysis is still used, and the only difference is that the cathode in Electrolytic Cell B is a pure titanium electrode. Take samples for analysis, and obtain that the conversion rate of the raw material acrylonitrile is 85%, the selectivity of the product hexamethylenediamine is 0%, the selectivity of propylamine is 0%, the selectivity of hexamethylenetriamine is 0%, and the selectivity of the main by-product adiponitrile is 84%.

[0072] Comparative Example 2

[0073] Compared with Example 2, the difference is that only the electrodes in Electrolytic Cell A are used for the first-stage electrolytic reaction. After reaching the end point, take samples for analysis, and obtain that the conversion rate of the raw material acrylonitrile is 87%, the selectivity of the product hexamethylenediamine is 0%, the selectivity of propylamine is 0%, the selectivity of hexamethylenetriamine is 0%, and the selectivity of the main by-product adiponitrile is 85%.

[0074] Comparative Example 3

[0075] Compared with Example 2, the difference is that only the first-stage electrolysis reaction of the A electrolytic cell is carried out, and the cathode of the A electrolytic cell is the prepared metal-doped modified titanium-based titanium dioxide array tube electrode, and the electrode preparation method is the same as that of Example 2. After reaching the end point, samples were taken for analysis, and the conversion rate of raw material acrylonitrile was 66%, the selectivity of the product hexamethylenediamine was 60%, the selectivity of propylamine was 4%, the selectivity of hexamethylenetriamine was 2%, and the selectivity of the main by-product adiponitrile was 26%.

[0076] Table 1 Raw material conversion rate and selectivity of each product

[0077] Number Acrylonitrile (%) Hexamethylenediamine (%) Adiponitrile (%) Propylamine (%) Hexanetriamine (%) Example 1 80 83 5 8 2 Example 2 90 88 3 4 4 Example 3 85 85 4 0.8 9 Example 4 77 35 45 10 4 Comparative Example 1 85 0 84 0 0 Comparative Example 2 87 0 85 0 0 Comparative Example 3 66 60 26 4 2

Claims

1. A method for electrochemically synthesizing hexamethylenediamine from acrylonitrile, characterized in that, the method comprises the following steps: (1) Mix acrylonitrile, quaternary ammonium base, phosphate, and water to prepare an electrolyte; (2) Pass the electrolyte into two electrolytic cells A and B for two-stage electrolytic reaction to obtain hexamethylenediamine.

2. The method according to claim 1, characterized in that, the quaternary ammonium base in step (1) is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltriethylammonium hydroxide, and adamantylammonium hydroxide; preferably, the content of the quaternary ammonium base in the electrolyte is 0.01 wt% - 5 wt%.

3. The method according to claim 1, characterized in that, the phosphate in step (1) is one or more of dipotassium hydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, and sodium dihydrogen phosphate; preferably, the content of the phosphate in the electrolyte is 5 wt% - 12 wt%.

4. The method according to claim 1, characterized in that, the content of acrylonitrile in step (1) is 1 wt% - 20 wt%; preferably, the content of acrylonitrile in the electrolyte is 5 wt% - 15 wt%.

5. The method according to claim 1, characterized in that, in step (2), both electrolytic cells A and B use single-chamber diaphragmless electrolytic cells, a DC power supply is used, and the electrolyte is subjected to an electrolytic reaction by a constant current method.

6. The method according to any one of claims 1 - 5, characterized in that, in the electrolytic cell A of step (2), the cathode is a lead electrode and the anode is a DSA electrode coated with iridium tantalum; and / or: The current density in the electrolytic cell A is 500 A / m 2 -3000 A / m 2 .

7. The method according to any one of claims 1 - 6, characterized in that, in the electrolytic cell B of step (2), the cathode is a nano-titanium dioxide array tube electrode and the anode is a DSA electrode coated with iridium tantalum; and / or: the current density in electrolytic cell B is 1500 A / m 2 - 3000 A / m 2 .

8. The method according to claim 7, characterized in that, the nano-titanium dioxide array tube electrode is prepared by anodizing a titanium sheet with a hydrofluoric acid solution as the anodizing solution; preferably, the concentration of the hydrofluoric acid solution is 0.01 wt% - 10 wt%, the anodizing voltage is 5 - 50 V, and the time is 0.5 - 2 h.

9. The method according to claim 7, characterized in that, in the electrolytic cell B of step (2), the cathode is a metal-doped modified titanium-based nano-titanium dioxide array tube electrode, preferably, the doped metal is one or more of In, Ir, Zn, Sn, Pb, Ce, Zr, Fe, and Cu; Preferably, the metal doping amount is 1-50 mg / cm 2 .

10. The method according to claim 9, characterized in that, the electrode of the electrolytic cell B is obtained by impregnating the nano-titanium dioxide array tube electrode with a metal salt aqueous solution and then calcining; preferably, the total mass fraction of the metal salt aqueous solution is 2 - 15 wt%, the impregnation time is 1 - 4 h; and / or: the calcination temperature after doping is 400 - 600 °C, and the time is 1 - 3 h.

Citation Information

Patent Citations

  • Rare-earth oxide modified high-selectivity catalyst for adiponitrile hydrogenation and hexylenediamine production, preparation method and application thereof

    CN109647419A

  • Electrocatalytic hydrogenations of nitriles to amines

    US5266731A

  • Method for electrosynthesis of adiponitrile by using dimensionally stable anode

    CN102061482A

  • Method for preparing adiponitrile by electrolyzing acrylonitrile on basis of plasmas

    CN110016690A

  • Method for preparing adiponitrile by safely and efficiently electrolyzing acrylonitrile in single-phase solution

    CN113774413A